EVALUASI PEMBELAJARAN MEMBACA KUTUB TURATS DI MADRASAH ALIYAH MAMBAUS SHOLIHIN SUCI MANYAR GRESIK - Mohammad Makinuddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
Abstract: this study will explore the evaluation of learning to read the turats / yellow book poles in Madrasah Aliyah Mambaus Sholihin. This simple research uses a qualitative approach and type of descriptive research. The results of the study found that the first conclusion: the evaluation of learning to read polar turats has the aim to collect various information on the development experienced by students after they follow the learning process as a guide to the level of ability and success of students and to measure and assess the effectiveness of teaching and various teaching methods used. has been implemented or implemented by educators, as well as learning activities carried out by students. Second: The type of evaluation used uses summative type of evaluation, which is an evaluation used to assess student acquisition at the end of teaching, this evaluation aims to determine the level of learning outcomes achieved by students after completing the learning material program within a certain period of time. Third: the evaluation aspect of learning to read the kutub turats includes reciting words or sentences in the kutub turats and capturing the meaning or understanding of the text in the kutub turats.Keywords: Evaluation, Reading, kutub turats